Three-dimensional echocardiographic evaluation of the right ventricle in patients with uncomplicated systemic lupus erythematosus. (April 2019) - Buonauro, A; Sorrentino, R; Esposito, R; Nappi, L; Lobasso, A; Santoro, C; Rivellese, F; Sellitto, V; Rossi, F W; Liccardo, B; Tufano, A; Galderisi, M; et al.
Our aim was to identify subclinical right ventricular (RV) alterations in systemic lupus erythematosus (SLE) by combining standard and three-dimensional echocardiography (3DE). Fifty SLE patients without concomitant cardiac disease and 50 healthy controls, matched for age and gender, were enrolled. Disease damage was evaluated by inflammatory markers and SLE damage index. All patients underwent an echo-Doppler examination with 3DE assessment of RV function, RV septal and lateral longitudinal strain. The two groups had comparable body mass index and blood pressure. RV transversal middle diameter and pulmonary arterial pressure were significantly higher in SLE compared to controls. By 3DE, RV end-systolic volume ( p  = 0.037) was greater, whereas stroke volume ( p  = 0.023), ejection fraction ( p  < 0.0001) and septal and lateral longitudinal strain (both p  < 0.0001) were lower in SLE. SLE damage index ≥ 1 was negatively associated with tricuspid annular plane systolic excursion (TAPSE) ( p  < 0.002), tricuspid E/A ratio ( p  = 0.003), RV ejection fraction ( p  < 0.05), lateral longitudinal strain ( p  < 0.0001) and septal longitudinal strain ( p  = 0.04). By separate multivariate models, after adjusting for age, C reactive protein and proBNP, SLE damage index was independently associated with TAPSE ( p  = 0.009) and RV lateral longitudinal strain ( p  = 0.007). In conclusion, a subclinical RV systolic dysfunction is detectable in SLE by 3DE, RV lateral wall strain being a key parameter. RV dysfunction is associated with cumulative disease damage.